2018
DOI: 10.1186/s40644-018-0170-8
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation of pancreatic neuroendocrine carcinoma from pancreatic ductal adenocarcinoma: the values of CT imaging features and texture analysis

Abstract: BackgroundImaging findings for pancreatic neuroendocrine carcinoma (PNEC) and pancreatic ductal adenocarcinoma (PDAC) often overlap. The aim of this study was to demonstrate the value of computed tomography (CT) imaging features and texture analysis to differentiate PNEC from PDAC.MethodsTwenty-eight patients with pathologically-proved PDAC and 14 patients with PNEC were included in this study. CT imaging findings, including tumor boundary, size, enhancement degree, duct dilatation and parenchymal atrophy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 19 publications
(24 reference statements)
0
34
1
Order By: Relevance
“…The ROIs we selected for the resection margin included normal pancreatic tissue and tumor tissue for radiomics methods analysis. We analyzed the images of the resection margin at three layers in patients with pancreatic head adenocarcinoma, rather than the entire tumor at a single layer as in other studies, 38,39 as different resection margins could re ect different tumor biological characteristics present within the heterogenous primary tumor. This makes our study more detailed and representative compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ROIs we selected for the resection margin included normal pancreatic tissue and tumor tissue for radiomics methods analysis. We analyzed the images of the resection margin at three layers in patients with pancreatic head adenocarcinoma, rather than the entire tumor at a single layer as in other studies, 38,39 as different resection margins could re ect different tumor biological characteristics present within the heterogenous primary tumor. This makes our study more detailed and representative compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Texture analysis is an emerging imaging-based post-processing method that allows for quantification of tissue heterogeneity (27). There has been a surge in recent years in the research application of CT texture analysis in tumor identification, staging, and therapy response assessment (19, 23, 27, 28). However, no studies have demonstrated the value of CT texture analysis in differentiating MFP from PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…FDT factor = 0.114858*FDA + 0.167196*WavEnHL_s-4 + 0.971237*DifEntr/LngREmph + 0.976915*ShrtREmp (11) FDA-WDT factor = 0.813578*FDA + 0.784505*WavEnHL_s-4 + 0.190267*DifEntr/LngREmph + 0.152573*ShrtREmp (12) where the values of the variables in the equation are standardized by subtracting their means and dividing by their standard deviations. It also shows the estimated communalities, which can be interpreted as estimating the proportion of the variability in each variable attributable to the extracted factors.…”
Section: Estimation Of Recurrencementioning
confidence: 99%
“…Texture analysis may be divided into four methods: statistical, structural, model-based, and transform [9,10]. TA is commonly used in medicine to analyse X-ray photos, computed tomography, or magnetic resonance images [11][12][13][14] Irregular shape is a characteristic feature of leukoplakia. The measurement of a leukoplasm's area and shape is very difficult, especially comparing measurements before and after treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation